OxyR contributes to virulence of Acidovorax citrulli by regulating anti-oxidative stress and expression of flagellin FliC and type IV pili PilA - Wang, Jianan; Liu, Jun; Zhao, Yuqiang; Sun, Minghui; Yu, Guixu; Fan, Jiaqin; Tian, Yanli; Hu, Baishi (Frontiers in Microbiology, 2022)
In many bacteria, OxyR acts as a transcriptional regulator that facilitates infection via degrading hydrogen peroxide (H2O2) generated by the host defense response. Previous studies showed that OxyR also plays an important role in regulating biofilm formation, cell motility, pili relate-genes expression, and surface polysaccharide production. However, the role of OxyR has not been determined in Acidovorax citrulli strain xjl12. In the current study, the qRT-PCR and western blot assays revealed that the expression level of oxyR was significantly induced by H2O2. The oxyR deletion mutant of A. citrulli was significantly impaired bacterial tolerance to oxidative stress and reduced catalase (CAT) activity. In addition, oxyR mutant resulted in reduced swimming motility, twitching motility, biofilm formation, virulence, and bacterial growth in planta by significantly affecting flagellin and type IV pili-related gene (fliC and pilA) expression. The qRT-PCR assays and western blot revealed that OxyR positively regulated the expression of fliC and pilA. Furthermore, bacterial one-hybrid assay demonstrated that OxyR directly affected pilA and fliC promoter. Through bacterial two-hybrid assay, it was found that OxyR can directly interact with PilA and FliC. These results suggest that OxyR plays a major role in the regulating of a variety of virulence traits, and provide a foundation for future research on the global effects of OxyR in A. citrulli.